Hilbert-Huang Transform Analysis Of Hydrological And Environmental Time Series - Rao, A. Ramachandra; Hsu, En-Ching.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
The Hilbert-Huang Transform ((HHT) is a recently developed technique which is used to analyze nonstationary data. Hydrologic and environmental series are, in the main, analyzed by using techniques which were developed for stationary data. This has led to problems of interpretation of the results. Environmental and hydrologic series are quite often nonstationary. The basic objective of the material discussed in this book is to analyze these data by using methods based on the Hilbert-Huang transform. These results are compared to the results from the traditional methods such as those based on Fourier transform and other classical statistical tests. Audience This book will be of value to researchers interested in climate change and advanced graduate students in civil engineering, atmospheric sciences and statistics.
Hilbert-Huang Transform (HHT) Spectral Analysis -- Hilbert-Huang Spectra Of Simulated Data -- Rainfall Data Analysis -- Streamflow Data Analysis -- Temperature Data Analysis -- Wind Data Analysis -- Lake Temperature Data Analysis -- Conclusions.
Keywords: HYDRAULIC ENGINEERING; DISTRIBUTION (PROBABILITY THEORY).; ENGINEERING MATHEMATICS; CLIMATIC CHANGES; ENVIRONMENTAL SCIENCES; GEOSCIENCES; HYDROGEOLOGY; CLIMATE CHANGE; MATH. APPL. IN ENVIRONMENTAL SCIENCE; MATH. APPLICATIONS IN GEOSCIENCES; APPL.MATHEMATICS/COMPUTATIONAL METHODS OF ENGINEERING; PROBABILITY THEORY AND STOCHASTIC PROCESSES